Cognitive, Language, and Behavioral Outcomes in Children With Autism Spectrum Disorders Exposed to Early Comprehensive Treatment Models: A Meta-Analysis and Meta-Regression - Shi, Bijun; Wu, Weijia; Dai, Meixia; Zeng, Jingjing; Luo, Jingyin; Cai, Li; Wan, Bin; Jing, Jin (Frontiers in Psychiatry, 2021)
Background Early comprehensive treatment models (CTMs) have been developed as effective treatments for children with autism spectrum disorder (ASD). Numerous studies have suggested that CTMs can improve short-term outcomes, but little is known about precise outcome information in childhood. The current meta-analysis reviewed studies reporting broader outcomes in children with ASD who had ever participated in a CTM and examined the predictors of developmental gains. Methods We searched eight databases up to June 13, 2019, for relevant trials and natural experiments. Longitudinal studies were selected if they investigated the outcomes of CTMs. Two meta-analyses were undertaken to provide a summary estimate of change in treatment outcomes and to evaluate the effect of CTMs; one used the standardized mean change between the pretest and posttest, and the other was a classical meta-analysis. Stratified and random-effects meta-regression analyses were performed to search for outcome differences among studies. Results Eighteen intervention studies (involving 495 children with ASD) met all the inclusion criteria: 12 used early intensive behavioral intervention (EIBI), and two used the Early Start Denver Model (ESDM). Outcomes were categorized into three parts: cognitive, language and behavioral (e.g., adaptive functioning and symptomatology). Overall, most children with ASD who had ever participated in an early CTM made gains in many areas of functioning, especially in terms of symptom- and language-related outcomes. Stratified analyses indicated that the ESDM displayed the largest effect on IQ improvement (ES=1.37, 95% CI: 0.95-1.80), while EIBI was more effective for symptom reduction (ES=-1.27, 95% CI: -1.96 to -0.58). Further meta-regression suggested that interventions with parent involvement, higher intensity, and longer treatment hours yielded greater improvements in IQ and social adaptive functioning, respectively. Conclusion The results demonstrate a positive association between CTMs and better prognosis in childhood, especially regarding symptoms and language. However, most extant research involves small, nonrandomized studies, preventing definitive conclusions from being drawn. Clearly, the outcomes of children with ASD are still far from normal, especially with respect to adaptive functioning, and the four mediating variables pertaining to treatment elements can affect their gains, including approach, implementer, intensity, and total treatment hours.